Arson and arsonists: Results from a study with a portuguese sample - Gonçalves, Rui Abrunhosa (2006)
The authors present data concerning the identification of Portuguese forest arsonists who were serving prison sentences for this crime. These offenders present several psychological features (alcohol abuse, mental illness, psychiatric care, low intelligence,...) and are issued from poor socio-economic backgrounds. No traces of antisocial or psychopathic personality were found. The authors also refer to necessity of taking a closer look to other causes of forest fires, mainly accidental 3nes, that account for a large proportion of occurrences and show that prevention is not functioning- well and negligent behaviours are riot considered for punishment, focusing on the importance of an environmental conscience that seems to be far away from the legislations trends on these matters.